2019
DOI: 10.3892/ijmm.2019.4094
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of curcumin against rats with focal cerebral ischemia-reperfusion injury

Abstract: The aim of the present study was to investigate the protective effects of curcumin and its effect on the methyl ethyl ketone/extracellular signal regulated kinase/cAMP-response element binding protein (MEK/ERK/cREB) pathway. The study was conducted in vivo and in vitro as follows: In vivo: Focal cerebral ischemia-reperfusion (IR) models of rats were made with the plug-line method. Adult male Sprague-dawley rats were divided into four groups: Sham operation control group, IR and curcumin-treatment groups (100 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
0
29
0
Order By: Relevance
“…In order to test a potential interplay between apoptosis and necroptosis in our models, we co-treated cells with the caspase-3 inhibitor, Ac-DEVD-CHO, and Nec-1. Since previous studies showed neuroprotective effects of curcumin in various types of neuronal cell damage (Mhillaj et al 2019;Szczepanowicz et al 2016) and the involvement of both apoptosis and necroptosis inhibition has been suggested to be associated with the curcuminmediated protection (Dai et al 2013;Wang et al 2017;Xu et al 2019), we studied a potential synergism in neuroprotective effects of Nec-1 and curcumin (Curc) in UN-and RA-SH-SY5Y cells. Next, we searched for putative mechanisms involved in neuroprotection mediated by Nec-1 by measuring the apoptotic markers (caspase-3 activity, AIF translocation), calpain activity (145 kDa cleavage product of spectrin α II) and lysosomal permeability (cathepsin D activity).…”
Section: Introductionmentioning
confidence: 99%
“…In order to test a potential interplay between apoptosis and necroptosis in our models, we co-treated cells with the caspase-3 inhibitor, Ac-DEVD-CHO, and Nec-1. Since previous studies showed neuroprotective effects of curcumin in various types of neuronal cell damage (Mhillaj et al 2019;Szczepanowicz et al 2016) and the involvement of both apoptosis and necroptosis inhibition has been suggested to be associated with the curcuminmediated protection (Dai et al 2013;Wang et al 2017;Xu et al 2019), we studied a potential synergism in neuroprotective effects of Nec-1 and curcumin (Curc) in UN-and RA-SH-SY5Y cells. Next, we searched for putative mechanisms involved in neuroprotection mediated by Nec-1 by measuring the apoptotic markers (caspase-3 activity, AIF translocation), calpain activity (145 kDa cleavage product of spectrin α II) and lysosomal permeability (cathepsin D activity).…”
Section: Introductionmentioning
confidence: 99%
“…Curcumin, with its neuroprotective effects and hardly existing toxicity, have become an attractive alternative treatment tool for various neurological disorders [15][16][17][18][19][20]. After systemic administration, curcumin can across the blood-brain barrier, and exert its therapeutic e cacy in the brain [25].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, in recent years, some agents with anti-apoptosis, antioxidant and anti-in ammatory properties have been expected to attenuate ACR-induced neurotoxicity [3,8,[11][12][13][14]. As the most active constituent in turmeric, a common spice, with a strong safety record, curcumin has been considered to be a potential natural neuroprotective agent under limelight [15][16][17][18]. Based on its known antioxidant, anti-in ammatory and anti-apoptosis activities, curcumin has been shown to protect the neurons against cerebral ischemiareperfusion injury [15,16], dysfunction linked with Parkinson's disease mediated by Bisphenol-A [19], sleepdeprivation induced memory impairments [20], and depression [21], etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, in recent years, some agents with antiapoptosis, antioxidant and anti-inflammatory properties have been expected to attenuate ACR-induced neurotoxicity [3,8,[11][12][13][14]. As the most active constituent in turmeric, a common spice, with a strong safety record, curcumin has been considered to be a potential natural neuroprotective agent under limelight [15][16][17][18]. Based on its known antioxidant, anti-inflammatory and antiapoptosis activities, curcumin has been shown to protect the neurons against cerebral ischemia-reperfusion injury [15,16], dysfunction linked with Parkinson's disease mediated by Bisphenol-A [19], sleep-deprivation induced memory impairments [20], and depression [21], etc.…”
Section: Introductionmentioning
confidence: 99%